The Legal Imperative of Bawaslu's Oversight in Enforcing Verdict Compliance - Nadeak, Pebby Pratiwi; Fikri, Sultoni; Akhtar, Imranullah (DiH: Jurnal Ilmu Hukum, 2025)
Election is a democratic means to elect leaders and representatives of the people, where Bawaslu has a strategic role as an election supervisory institution. Bawaslu is tasked with ensuring that each stage of the election is in accordance with laws and regulations, with the legal basis listed in Law No. 7 of 2017. As a quasi-judicial institution, Bawaslu has the authority to issue decisions that are final and binding. However, in practice, the implementation of follow-up to Bawaslu decisions often faces challenges, such as disobedience or suboptimal implementation by the KPU and related parties. This study aims to examine the urgency of legal certainty in supervising the implementation of Bawaslu decisions and to determine the ideal model of supervision to fulfill the principle of legal certainty. The method used is normative juridical with a legislative approach, with primary and secondary data sources. The results of the study show that there is a legal vacuum that hinders the optimal implementation of the decision. Therefore, this study emphasizes the urgency of an integrated supervision model with strict evaluation and sanction mechanisms, which can increase compliance with Bawaslu decisions and ensure the implementation of elections in accordance with legal provisions.